STRUKTUR NARASI, FUNGSI DAN NILAI BUDAYA DALAM KUMPULAN LEGENDA DI KALIMANTAN TENGAH - Andreow Kony Darlam Bagus (Universitas Lambung Mangkurat, 2019)
Narrative Structure, Function, and Cultural Values in Legends of CentralKalimantan. Research entitled is motivated by the interest of researcher topreserve the legend of the area that is now almost extinct and forgotten by thecommunity. This study aims to describe (1) the structure of narrative in legends ofcentral kalimantan, (2) the function of legend in legendsof central kalimantan, (3)cultural values in legends of central kalimantan. This research used a descriptivemethod. the data source can be from fifteen legends in central kalimantan creationby Prof. Drs. Kumpiady Widen, MA, Ph. D then collected through severaltechniques, classified, analyzed, and concluded. Based on the results of dataanalysis, it can be concluded that of the fifteen legends that have been analyzed,there are ten local legends and five individual legends. Based on analysis of thenarrative structure, the five narrative stages are found from the fifteen legends.Based on analysis of legend’s function, the six functions of legend used as theory inthis study, only found four functions of legend, the function of legend to help theeducation of young people, increase feelings of solidarity of group, socialsanctions for people who behave well or punish, and last as a means of socialcriticism. based on analysis of the cultural values contained in these fifteen legendsfound five cultural values, namely: the cultural values of human life, the culturalvalues of human works, the cultural values of human perceptions of time, thecultural values of the human view of nature and the latter are cultural valueshuman relationships with others. Key words: naration structure, legendary function, culture values Abstrak Struktur Narasi, Fungsi, dan Nilai Budaya dalam Kumpulan Legenda diKalimantan Tengah. Penelitian ini dilatarbelakangi oleh ketertarikan penelitiuntuk melestarikan legenda daerah yang sekarang sudah hampir punah dandilupakan oleh masyarakat. Penelitian ini bertujuan mendeskripsikan (1) Strukturnarasi dalam kumpulan legenda di Kalimantan Tengah (2) Fungsi legenda dalamkumpulan legenda di Kalimantan Tengah (3) Nilai Budaya dalam kumpulanlegenda di Kalimantan Tengah. Penelitian ini menggunakan metode deskriptif. Sumber data didapat dari lima belas legenda yang ada di Kalimantan Tengahkarya Prof. Drs. Kumpiady Widen, MA, Ph. D. Berdasarkan analisis mengenaistruktur narasi, kelima tahap narasi ditemukan dari lima belas legenda tersebut.Berdasarkan analisis mengenai fungsi legenda, dari enam fungsi legenda yang dijadikan teori dalam penelitian ini hanya ditemukan empat fungsi legenda.Berdasarkan analisis mengenai nilai budaya yang terkandung dalam kelima belaslegenda tersebut ditemukan lima nilai budaya, yaitu nilai budaya tentang hidupmanusia, nilai budaya tentang karya manusia, nilai budaya persepsi manusiatentang waktu, nilai budaya pandangan manusia terhadap alam dan yang terakhirnilai budaya hubungan manusia dengan sesama. Kata-kata kunci: struktur narasi, fungsi legenda, nilai budaya